Oral Contraceptives and HRT Risk of Thrombosis. (March 2018) - Gialeraki, Argyri; Valsami, Serena; Pittaras, Theodoros; Panayiotakopoulos, George; Politou, Marianna
Estrogen-containing medication, prescribed either for contraception in women of reproductive age or for prevention of cardiovascular events and osteoporosis as well as for alleviation of symptoms related to menopause, is associated with changes in the hemostatic balance and contributes to increased risk of development of venous thromboembolic complications. This risk is dose and medication dependent, increases with age, congenital and/or acquired predisposition to thrombosis, and mode of administration. This review attempts to summarize the current knowledge regarding the pathophysiology of oral contraceptive (OC) and hormone replacement therapy (HRT) -induced prothrombotic state in women, the risk of thrombosis associated with administration of various commercially available OCs and HRT, the additional risk in women with hereditary or acquired thrombophilia, and the currently available recommendations regarding massive screening of women for thrombophilia prior to initial prescription or continuation of treatment with OCs and HRT preparations.